Ideologi Islam Tradisionalis Pada Tafsir Al-Ibriz dan Al-Iklil - Mukminin, Moh. Amiril; Irbathy, Shafa Alistiana (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
This article discusses the Tafsir Nusantara works of Bisri Mustofa (1915–1977) titled Al-Ibriz li Ma’rifat al-Qur’an al-Aziz and Misbah Mustofa (1916–1994) titled Al-Iklil fi Ma’ani al-Tanzil. Both scholars share a similar background, originating from the island of Java and shaped by the traditional pesantren (Islamic boarding school) education system. The main problem examined in this study is the ideology of traditionalist Islam found in these two interpretations. The study concludes that traditionalist Islam remains dynamic in its understanding of religious, traditional, and cultural phenomena. This is evident in the differing perspectives of the two scholars despite their shared background, they express distinct viewpoints. One example is their interpretation regarding the tahlil tradition. Misbah Mustofa presents a more specific and somewhat critical view of tahlil, while Bisri Mustofa’s interpretation does not critique it, implying that he perceives no significant problem in the practice.